(untitled) - Finkelstein, Leo (Boston, MA., 2005)
The focus of this text is to teach engineering students the skill of technical writing. It takes a project oriented approach and covers writing functions that are of particular use to the engineering student
Keywords: Technical writing; Handbooks, manuals, etc